Reducing Students` Speaking Anxiety by Using Role-Play Technique - Nurwahida, Nurwahida; Ardin, Hardiani; Riskatul Fadliyah; Rahmiati, Rahmiati (AIJER: Algazali International Journal Of Educational Research, 2024)
One technique proven to enhance students' speaking abilities is the use of role-play technique. This research aimed to give a more thorough description of factors causing speaking anxiety on students and how role-play technique can be used to reduce their anxiety in speaking. This research is a literature study by collecting several articles or journals from different trusted sources related to the notion of factors causing speaking anxiety and the effect of role-play in reducing student’s anxiety in speaking. The findings were carrying out with some stages starting from searching and finding relevant data, analysing the data obtained, and finally presenting ideas from the findings. The result of this research showed that there were several factors causing anxiety on the students` speaking performances such as (1) lack of preparation, (2) lack of self-confidence, (3) poor pronunciation, (4) low English proficiency, (5) fear of negative evaluation,(6) fear of making mistakes, (7) fear of being laughed at, (8) fear of facing the unpredictable question, (9) limited grammatical knowledge, and (10) undeveloped vocabulary. In addition, the results of this research revealed that using role-play techniques in the teaching-learning process could help the students reduce their speaking anxiety in the classroom.